2023
DOI: 10.3390/plants12173171
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identified MADS-Box Genes in Prunus campanulata ‘Plena’ and Theirs Roles in Double-Flower Development

Chaoren Nie,
Xiaoguo Xu,
Xiaoqin Zhang
et al.

Abstract: The MADS-box gene family plays key roles in flower induction, floral initiation, and floral morphogenesis in flowering plants. To understand their functions in the double-flower formation of Prunus campanulata ‘Plena’ (hereafter referred to as PCP), which is an excellent flowering cherry cultivar, we performed genome-wide identification of the MADS-box gene family. In this study, 71 MADS-box genes were identified and grouped into the Mα, Mβ, Mγ and MIKC subfamilies according to their structures and phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Gibberellin promotes stamen development in A. thaliana by promoting the expression of MYB TFs, which are controlled by jasmonic acid [74]. The gibberellin, abscisic acid, salicylic acid, and methyl jasmonate (MeJA) signaling pathways may interact with cis-acting elements in the promoter region of the MADS-box gene to regulate stamen and petal development [34,75]. Studies have shown that ethylene is critical in determining plant reproductive organs.…”
Section: Plant Hormones Regulate Stamen Petaloidmentioning
confidence: 99%
See 2 more Smart Citations
“…Gibberellin promotes stamen development in A. thaliana by promoting the expression of MYB TFs, which are controlled by jasmonic acid [74]. The gibberellin, abscisic acid, salicylic acid, and methyl jasmonate (MeJA) signaling pathways may interact with cis-acting elements in the promoter region of the MADS-box gene to regulate stamen and petal development [34,75]. Studies have shown that ethylene is critical in determining plant reproductive organs.…”
Section: Plant Hormones Regulate Stamen Petaloidmentioning
confidence: 99%
“…Whereas on the other hand, phytohormones can affect the growth and development of floral organs by regulating the expression of genes in their signal transduction and synthesis pathways [32][33][34]. For example, auxin regulates the expression of AUX/IAA, ARF, and GH3, thereby affecting cell expansion and division, cell elongation and differentiation, and various physiological responses [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation